2003
DOI: 10.1001/archopht.121.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Eye Drop Characteristics

Abstract: Objective: To determine the importance that patients place on the characteristics of topical therapy for lowering intraocular pressure. Methods:We administered a willingness-to-pay instrument to 230 patients from 4 glaucoma subspecialty practices, asking them how much they would be willing to pay to obtain particular characteristics in an eye drop. Data about the subjects' demographics, economic status, attitudes toward eye drops and systemic medications, and symptoms from eye drops were correlated with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 12 publications
2
35
1
1
Order By: Relevance
“…In fact, compliance rates near 90% have been reported in some studies, with 85% to 92% of patients reporting no to very few missed doses during the study period. 55,56 However, these studies relied on patient self-reporting, which has been shown to overestimate compliance dramatically. 17,19,57 Another study found that in the 3 years following a glaucoma diagnosis, less than 10% of patients refilled their initial prescription regularly.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, compliance rates near 90% have been reported in some studies, with 85% to 92% of patients reporting no to very few missed doses during the study period. 55,56 However, these studies relied on patient self-reporting, which has been shown to overestimate compliance dramatically. 17,19,57 Another study found that in the 3 years following a glaucoma diagnosis, less than 10% of patients refilled their initial prescription regularly.…”
Section: Discussionmentioning
confidence: 99%
“…These other methods of measuring utility values may be more susceptible to the influence of the subjects' socioeconomic or educational background. 14,15 Diabetic retinopathy and impact on quality of life A Gabrielian et al…”
Section: Definitions and Scoringmentioning
confidence: 99%
“…Olgunun hat›rlamayla ilgili güç-lükleri ve hekim karfl›s›nda mahcup olmak istememe e¤i-liminden dolay› bu yöntemin kullan›ld›¤› çal›flmalarda elde edilen THU oranlar›n›n gerçekte var olandan daha yüksek bulundu¤u bildirilmektedir (8,16). Hastan›n ifadesi esas al›narak yap›lan çal›flmalarda, THU %25 ile %92 aras›nda de¤iflmektedir (12,13,(17)(18)(19)(20). Bildirilen oranlar aras›nda büyük farkl›l›klar›n olmas›, THU'nun farkl› flekillerde tan›m-lamas›na ve çal›flmalar›n de¤iflik sosyokültürel yap›daki olgularla gerçeklefltirilmesine ba¤lanabilir.…”
Section: Tart›flmaunclassified